Strengthening Project profile Pancasila students for Developing Students' Collaborative Skills - Ahmad Muhibbin; Rezalfa Isro Khoirunisa (Jurnal Penelitian Pendidikan IPA, 2023)
Research purposes This is describe strengthening project profile internal Pancasila students’ application of collaborative skills, obstacles and solutions for cope obstacles encountered student oriented outlook global diversity. Study This use shortethane descriptive qualitative. Subject study This head schools, head of student affairs, Civics teachers, and students. Data collection techniques are interviews, observation and documents. Validity of data use triangulation sources and triangulation technique. Data analysis using interactive models. Research result i.e. Along with rapidly development technology in the 21st century, students No only required for understand aspect cognitive, but also skills like think critical and collaborative. Internal constraints dimensions global diversity at SMA Negeri 1 Jatinom that is its limitations time, lack of source Power. The solution at hand with apply approach involved learning _ student in a way active in activity collaborative. How to apply in character everyday life that is built and brought to life in self individual every student through culture school, learning intracurricular, cocurricular, or extracurricular at school